2013
DOI: 10.1038/onc.2013.152
|View full text |Cite
|
Sign up to set email alerts
|

CD99 suppresses osteosarcoma cell migration through inhibition of ROCK2 activity

Abstract: CD99, a transmembrane protein encoded by MIC2 gene is involved in multiple cellular events including cell adhesion and migration, apoptosis, cell differentiation and regulation of protein trafficking either in physiological or pathological conditions. In osteosarcoma, CD99 is expressed at low levels and functions as a tumour suppressor. The full-length protein (CD99wt) and the short-form harbouring a deletion in the intracytoplasmic domain (CD99sh) have been associated with distinct functional outcomes with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 62 publications
8
43
0
3
Order By: Relevance
“…Previous studies have reported that the cytoskeleton linker ezrin provides an early survival advantage for OS cells colonizing the lung, 29 and CD99 suppresses OS cell migration by inhibiting ROCK2, 30 In addition to EPLIN, we demonstrated that SATB2 regulates the expression of additional genes associated with cytoskeletal dynamics and adhesion such as ABI3, GSN and FMN2. The pathways altered by SATB2 are similar to those identified in breast cancer cells lacking SATB1.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have reported that the cytoskeleton linker ezrin provides an early survival advantage for OS cells colonizing the lung, 29 and CD99 suppresses OS cell migration by inhibiting ROCK2, 30 In addition to EPLIN, we demonstrated that SATB2 regulates the expression of additional genes associated with cytoskeletal dynamics and adhesion such as ABI3, GSN and FMN2. The pathways altered by SATB2 are similar to those identified in breast cancer cells lacking SATB1.…”
Section: Discussionsupporting
confidence: 52%
“…Epithelial tumors invade collectively, with duct-like patterns and E-cadherin and b-catenin positive cell-cell junctions, with or without lumen formation, and with or without up-regulation of EMT markers, including Twist and Zeb1 (Cheung et al 2013;Bronsert et al 2014). Furthermore, both E-and N-cadherin can orchestrate AJs and cell-cell interactions in cancer cells (Bronsert et al 2014;Zucchini et al 2014). Besides cadherins, Ig superfamily members and ephrins/EpH receptor systems were implicated in mediating more labile or transient cell-cell interactions in cancer cells (Cavallaro and Christofori 2004;Haeger et al 2014;Krusche et al 2016).…”
Section: Collective Cell Migration By Cell -Cell Junction Regulationmentioning
confidence: 99%
“…Overexpression of ROCK has been described in many solid tumors, including hepatocellular carcinoma [18], osteosarcoma [19,20], breast cancer [21], testicular cancer [22], bladder cancer [23] and also colon cancer [24]. In addition, several studies have emphasized the antimigratory and anti-invasive activity due to ROCK inhibition [25,26,27,28] or silencing [18,24,29,30], reinforcing the association between the Rho-ROCK axis and cancer.…”
Section: Introductionmentioning
confidence: 99%